Feminist-Kaleckian macroeconomic policy for developing countries - Stephanie Seguino; Caren A. Grown (Levy Economics Institute of Bard College, 2006)
This paper reviews evidence of the gender effects of globalization in developing economies. It then outlines a set of macroeconomic and trade policies to promote gender equity. The evidence suggests that while liberalization has expanded women's access to employment, the long-term goal of transforming gender inequalities remains unmet and appears unattainable without state intervention in markets. This paper sets forth some general principles that can produce greater gender equality, premised on shifting from economies that are profit led and export oriented to those that are wage led and full-employment oriented. The framework is Kaleckian in its focus on the relationship between the gender distribution of income and macroeconomic outcomes.
Keywords: F4; J2; O11; O2; 330; gender; income distribution; well-being; industrial policy; foreign direct investment; trade; macroeconomic policy